Agentes locales y proyectos transfronterizos en el eje transpirenaico Barcelona-Toulouse - Oliveras González, Xavier; Durà Guimerà, Antoni (Geographicalia, 2014)
Local public actors, as the nearest territorial administration, can detect needs and conflicts, but may not have the administrative competences for managing them. The paper shows territorial projects proposal and rejection to higher administrations in a cross-border context. The analysis focuses on the Transpyrenean axis of Barcelona-Toulouse (Spain-Andorra-France border), and in two different political and administrative contexts: before and after the juridical regulation of cross-border cooperation. Six examples are analysed, that are related to transport infrastructure (the Barcelona-Toulouse railway line, and the E-09 road), healthcare (the Cross-Border Hospital of Cerdanya) and water management (diversions of water and water treatment plants in upper Segre basin). It is evaluated the contribution of the actors and projects to cross-border regional construction.